Predicting attitudes toward infidelity based on lifestyles and communication patterns in working women - eltiaminia, nematollah (Psychology of Woman Journal, 2020)
This research was conducted to determine the predictive contribution of family communication styles and lifestyles on the tendency to marital infidelity in working women. The current research was descriptive and correlational. The statistical population of the research was made up of all working women of Lar city in 2018. Among the statistical population, 200 people were selected and studied by single-stage cluster sampling. Questionnaires of family communication styles, lifestyles, and tendency to marital infidelity were used to collect data. After collecting and extracting data, participants’ scores were analyzed using Pearson’s correlation coefficient and multiple regression analysis. The results showed a significant relationship between the dimensions of family communication styles and the dimensions of lifestyles with a tendency to marital infidelity in working women. Also, the results showed that the dimensions of family communication styles (dialogue and harmony) and lifestyles (environmental health and social health) significantly predict the tendency to marital infidelity in working women.